Visual Literacy to Foster Critical Thinking (2021)
ABSTRACT:This action research study was aimed at fostering critical thinking skills through visual literacy in a children's EFL course at a university extension program. Data were collected through a research journal, two interviews with the cooperating teacher, a focus group, and a students’ production activity. Data analysis showed that static images are an effective tool to foster learners’ critical thinking skills considering the students’ foreign language limitations and the teaching modality. Analysis also confirmed the importance of the teacher’s role in this process to select suitable images and design the appropriate questioning technique that encourages participation and skills development. An interesting option for further research could be using motion images for critical analysis and debate multiple situations in context.